2019
DOI: 10.1111/cea.13340
|View full text |Cite
|
Sign up to set email alerts
|

A reintroduction of environmental mite allergen control strategies for asthma treatment and the debate on their effectiveness

Abstract: SummaryAsthma affects three hundred million people worldwide. The effectiveness of house dust mite allergen control for asthma treatment is debatable. One aspect that has been little discussed in existing meta‐analyses is the possible role of environmental strategies. Here, we reintroduce the previously defined strategies for mite allergen control and discuss their importance to the debate on clinical effectiveness. The strategy of concurrent bedroom interventions is related to the combined use of a priori def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…The most recent Cochrane meta-analysis published in 2008 included 54 clinical trials which evaluated the efficacy of chemical methods, physical barriers, or the combination of different mite allergen avoidance measures on asthma control; the authors concluded that mite avoidance had no significant benefit on different asthma outcomes (lung function, symptoms, or anti-asthma medications use) [56]. The authors concluded that strategies aimed to reduce exposure to mite allergens cannot be recommended to mite-allergic patients with asthma, raising uncertainty and a considerable disagreement among clinicians and experts [58][59][60][61]. Furthermore, findings from a recent systematic reviews which included 67 trials (8 of which not randomized) evaluating single (37 trials) or multicomponent avoidance strategies (30 trials) showed inconclusive results or no benefit in asthma [57].…”
Section: Systematic Reviews and Meta-analysesmentioning
confidence: 99%
“…The most recent Cochrane meta-analysis published in 2008 included 54 clinical trials which evaluated the efficacy of chemical methods, physical barriers, or the combination of different mite allergen avoidance measures on asthma control; the authors concluded that mite avoidance had no significant benefit on different asthma outcomes (lung function, symptoms, or anti-asthma medications use) [56]. The authors concluded that strategies aimed to reduce exposure to mite allergens cannot be recommended to mite-allergic patients with asthma, raising uncertainty and a considerable disagreement among clinicians and experts [58][59][60][61]. Furthermore, findings from a recent systematic reviews which included 67 trials (8 of which not randomized) evaluating single (37 trials) or multicomponent avoidance strategies (30 trials) showed inconclusive results or no benefit in asthma [57].…”
Section: Systematic Reviews and Meta-analysesmentioning
confidence: 99%
“…In addition to the substantial meta-analysis by Gøtzsche and Johansen [7], several other meta-analyses on mite allergen avoidance for the treatment of asthma report varying results for the effectiveness of avoidance [8][9][10][11]. The variation in the complex interventions as well as the heterogeneity of several study outcomes urges further exploration [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of clinical benefits of textile-based avoidance strategies has not been demonstrated in rigorous systematic reviews [3][4][5]. In a scoping review, Boven et al [6] observed potential success with the strategy of air purification for the treatment of house dust mite allergy-related asthma. Previously, Mc-Donald et al [7] reported improvements in asthma symptom scores (ASS) associated with air purification in a small patient subgroup (n = 88).…”
Section: Introductionmentioning
confidence: 99%